The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.22260/isarc2019/0113
|View full text |Cite
|
Sign up to set email alerts
|

PPEs Compliance Technology to Legalize the Automated Monitoring of Safety Standards

Abstract: Governments are always looking to monitor safety violations on construction sites. Those violations are not only causing numerous injuries and deaths to workers but also delays and subsequently costs to the project developers. In the hierarchy of control, personal protective equipment (PPE), albeit the least effective, is still one of the most visible and therefore fundamental controls to protect workers from workplace hazards. While PPE should be monitored at all times by the related authorities and project o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…50 This reasoning was followed in Habbal et al, as the IACtHR decided that 'the revocation of Resolution 1088 constituted an adequate reparation'. 51 However, a glaring omission in the IACtHR's consideration was its Ivcher-Bronstein v Peru ('Ivcher-Bronstein') ruling. In Ivcher-Bronstein, the State also acted on the IACommHR's recommendations and revoked the order that denaturalised the Petitioner, 13 years after the fact.…”
Section: B Reparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…50 This reasoning was followed in Habbal et al, as the IACtHR decided that 'the revocation of Resolution 1088 constituted an adequate reparation'. 51 However, a glaring omission in the IACtHR's consideration was its Ivcher-Bronstein v Peru ('Ivcher-Bronstein') ruling. In Ivcher-Bronstein, the State also acted on the IACommHR's recommendations and revoked the order that denaturalised the Petitioner, 13 years after the fact.…”
Section: B Reparationsmentioning
confidence: 99%
“…On the question of nationality, the IACtHR reaffirmed its previous jurisprudence in stating that nationality is 'a prerequisite for the exercise of certain rights and is also a non-derogable right' 61 and that arbitrary deprivation of nationality deprives individuals of their civil and political rights. 62 The significance of this ruling should be assessed in light of developments at other human rights bodies. In a 2018 case concerning arbitrary deprivation of nationality, Anudo Ochieng Anudo v Tanzania ('Anudo'), the African Court on Human and Peoples' Rights established that international law permits loss of nationality only when specific conditions are met.…”
Section: B Reparationsmentioning
confidence: 99%
“…In general, all construction workers must wear a safety helmet and safety shoes [18]. Research conducted by Melzner (2012) reported that wearing appropriate safety equipment contributed to a reduction of fall accidents of more than 30% [19].…”
Section: Introductionmentioning
confidence: 99%